Development and application of functionalized polymeric materials for heavy metal ions recovery from industrial and mining wastewaters - Saad, Dalia (My University, 2014)
Water pollution is a serious environmental crisis all over the world hence unsafe water is rated among the top ten risks to health. Heavy metals are among the most threatening water contaminants because of their toxic effects on human health. This research was dedicated to the development of insoluble polyethylenimine derivatives; with the suitable functionalities for use as adsorbents to abstract specific toxic elements from mining and industrial wastewater. Branched polyethylenimine (PEI), well known for its metal chelating potential, was cross linked by epichlorohydrin in order to convert it into a water-insoluble form. The water-insoluble property gives the advantage of being used in situ and a possibility of regeneration and re-use, making it a more feasible and cost-effective method. Its surface was then modified for selective removal of uranium (U), mercury (Hg, arsenic (As), and selenium (Se). Three different functional groups were chosen according to the targeted elements namely: the phosphate group for selective removal of U and As; sulphate group for selective removal of Hg and Se, and the thiol group for selective removal of Hg. The adsorption performance of the developed materials was assessed in batch and column experiments. The selectivity of the synthesized materials as well as their ability to be regenerated for reuse was assessed. The results obtained demonstrated that the phosphonated derivative had a superior selectivity towards U with up to 99% adsorption (at pH 3 and 8) even in presence of competing ions, as well as a very good removal for As showing 88%. However, the removal mechanism of U by phosphonated cross-linked polyethylenimine (PCPEI) was found to be different from that of As in that while U was adsorbed onto PCPEI by complexation with the phosphate, As was adsorbed via anion replacement of the phosphate. The sulphonated derivative (SCPEI) was found to be very selective towards both Hg and Se giving removal percentages of 87% and 81% respectively (at pH 3 and 8). Interestingly, the performance of SCPEI towards Hg and Se is similar in both single (Hg or Se) or multi removal (Hg and Se), hence the mechanism is totally different. The thiolated derivative revealed a superior selectivity for Hg with 97% adsorption at pH of 3 and 8. Its adsorption capacity far exceeded that for the sulphonated derivative as a result of high affinity for Hg by the thiol group. The Langmuir and Freundlich isotherm models were used to interpret the adsorption nature of the metal ions onto the synthesized polymers. The Freundlich isotherm was found to best fit and describe the experimental data, thus implying adsorption onto heterogeneous surfaces. The kinetic rates were modelled using the pseudo first-order equation and pseudo second-order equation. The pseudo second-order equation was found to explain the adsorption kinetics most effectively, implying chemisorption. This was confirmed by the thermodynamic study which revealed that the adsorption process was accompanied by high activation energies (> 41 kJ mol-1). Desorption was conducted using 5 mol L-1 HNO3 for Hg and Se on SCPEI; 7 mol L-1 for U and As on PCPEI and 5 mol L-1 for Hg on TCPEI. The results pointed to a good desorption capacity using this solution and on re-use, the polymers still exhibited commendable adsorption. This desorption-re-use was done in five cycles, with only a small percentage loss in adsorption capacity. A continuous fixed-bed adsorption study was carried out using PCPEI (as one of the most efficient developed adsorbent) to assess the possibility of using these materials in filter systems for household use. The results obtained demonstrated that the performance of PCPEI in a fixed-bed column is dependent on the inlet concentration, flow rate, and bed height studied while the full description of breakthrough was accomplished by the Thomas and Yoon-Nelson models. The model constants belonging to each model were determined by linear regression and were proposed for use in column design. The problem of swelling that is usually associated with these resin-types of polymer was overcome by functionalization, a process similar to vulcanisation of rubber. There were no observed changes in the physical aspects of the polymers. The developed polymeric materials showed good results and potential to be applied for selective remediation of aqueous systems polluted by heavy metals. The study of adsorption in column systems showed that these materials have potential for use in filter systems for household taps, especially for communities accessing polluted drinking water sources.